(untitled) (Clinics, 2022)
Objective: Empyema is a complication of talc-pleurodesis that may lead to further surgical intervention and death. Therefore, the present study's objective was to identify the risk factors for the development of post-pleurodesis empyema after talc slurry pleurodesis in order to better select patients for this procedure and minimize its morbidity. Methods: Patients with malignant pleural effusion who underwent talc slurry pleurodesis at the present institution from January 2018 to January 2020 were retrospectively analyzed. Post-pleurodesis empyema was defined as pleural infection up to 30 days after pleurodesis. Using Cox regression analysis, significant prognostic factors for the development of empyema were examined. Results: Of the 86 patients identified for inclusion in the study, 62 were women (72%). Their mean age was 56.3±12.6 years. The median pleural drainage time was 9 days, and 20 patients (23.3%) developed empyema. In the univariate analysis, both drainage time (p = 0.038) and the use of antibiotics prior to pleurodesis (p < 0.001) were risk factors for pleural empyema. Multivariate analysis also identified the use of antibiotics as an independent risk factor (Odds Ratio [OR] 9.81; 95% Confidence Interval [95% CI] 2.87‒33.54). Although the pulmonary expansion was not associated with empyema in the multivariate analysis, patients with less than 50% pulmonary expansion had a 4.5-times increased risk of empyema (95% CI 0.90‒22.86; p = 0.067), and patients with 50‒70% pulmonary expansion had a 3.8-times increased risk of empyema (95% CI 0.98‒15; p = 0.053) after pleurodesis. Conclusion: The study suggests that antibiotic therapy prior to talc slurry pleurodesis may increase the risk of developing empyema. Furthermore, pleurodesis should be considered with caution in patients with long-duration chest tube placement and incomplete lung expansion.